PERILAKU SOSIAL ANAK USIA DINI DI LINGKUNGAN LOKALISASI GUYANGAN 2016 - TRI A., FAJAR LUQMAN (Program Studi Magister Pendidikan Anak Usia Dini, 2016)
This research aimed to describe the social behavior of children aged 5-6 years in theLocalization Guyangan Bagor Nganjuk District of East Java. The study was conducted to earlychildhood schooling in kindergarten Pertiwi Guyangan village. There are three main subfokus studiedwere the first form of social behavior, the process of internalization, and three factors supporting andinhibiting the formation of social behavior. The study used a qualitative approach to the type of casestudy method. Analysis of the data used that model of Miles and Huberman with data collectiontechniques using observation, interviews, and documentation. Subjects The study focused on childrenaged 5-6 years amounted to two people. The results showed a positive form of social behavior thatdevelops between the two subjects, namely research cooperation, generosity, caring and adaptable tonew people. There was also a negative social behavior is the behavior of the authorities, thedependency will love the attention of others and antagonism of the sexes. The process of internalizingsocial behavior of which is formed through gift giving, the punishment and the process of imitation.Parenting applied by parents is the subject of research using authoritarian and permissive parentingstyle is accompanied by violence in applying the rules.